Peningkatan Mutu “Papie-Sue” melaui Pendekatan GMP, SSOP, dan HACCP” - Siswara, Hamzah Nata; Huda, Khoirul; Wulandari, Kartika; Widiyanto, Slamet; Kholil, Abdul (Jurnal Pengabdian Masyarakat Charitas, 2024)
Papie-Sue is a diversification of agricultural and livestock products. Papie-Sue means banana pie with etawa milk. The main raw material for pie crust comes from banana flour, and the raw material for vla comes from etawa goat's milk. In addition, there are variations in flavors from local fruits, namely starfruit and durian. All raw materials and variations in flavors are local products of Bojonegoro. Because this product is processed from fresh ingredients without preservatives, a method is needed to maintain product quality until it reaches consumers. To improve the quality of Papie-Sue, GMP, SSOP, and HACCP are implemented through training and mentoring for the production team. The implementation of a food safety system based on GMP, SSOP, and HACCP can improve product quality by avoiding food contamination both biologically, chemically, and physically. Potential contamination will be identified to carry out prevention processes during the production process. Training participants consist of a production team of 15 people. The implementation of this food safety system is expected to be one way in the process of increasing the scale of the Papie-Sue business at SMKN Ngambon.